????? ?????? ???????? ??????? (????? ????? ????? ??? ?????? ????? ??????) - Mirwan Ahmad Taufiq (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2016)
Abstract: This study aims to discover that the real life of Sudanese students are still using both of kind of Arabic language; the Standard Arabic and the Slang Arabic in their daily activity and daily education in school. It is like the phenomena of diglossia in social bilingualism that has been studied by Joshua Fishman in early 1959, that there are two or several types of language in each community but the aspects effect kind of these types are different. Thus, this study tries to analyze and find the aspect could make them speak by both types of language in Arabic environment. This study has been conducted in Sudan in early 2016 addressed pupils in Elementary School El-Inqaz which was founded in 1992 at the Capital of Sudan, Khartoum. The reseacher has held oral test in standart Arabic to several students of that school, by listing some arabic vocabularies and arabic sentences and asking them to read the word and the sentences by their own language. In this way, the reseacher could datas of their Arabic spoken in daily activity and education. The second, the reseacher has interviewed them dealing with their daily activity in home, their parent language and tribe. It was done to know the environtment of the student. Abstrak: Kajian ini bertujuan untuk menngungkap fakta bahwa siswa Sudan masih menggunakan dua bentuk Bahasa Arab, Fusha dan Amiyah dalam kehidupan sehari-hari dan pendidikan di sekolah. Phenomena ini sering disebut sebagai Diglosia dalam sosial berbahasa yang pernah dikaji oleh Joshua Fishman pada awal 1959, bahwa ada dua standar bahasa yang digunakan pada setiap komunitas dengan berbagai aspek pengaruh yang berbeda-beda. Oleh karena itu kajian ini akan meneliti dan menganalisa beberapa aspek yang mendorong para siswa berbahasa Fusha dan Amiyah di lingkungan Arab. Penelitian ini dilakukan di Sudan pada awal tahun 2016, yang meneliti para siswa Sekolah Dasar El-Inqaz di Ibu kota Sudan, Khartoum. Peneliti telah melakukan tes lisan kepada siswa-siswa di sekolah itu, dengan mencantumkan kosa-kata Arab dan kalimat-kalimat Arab dan meminta mereka untuk mengucapkannya dengan bahasa mereka sendiri. Dengan cara ini, peneliti mendapatkan data-data tentang Bahasa Arab yang mereka ucapkan sehari-hari. Kedua, peneliti melakukan interview kepada mereka menanyakan bahasa keseharian mereka dan orang tua di rumah. Hal ini dilakukan agar dapat diketahui bentuk dan suasana lingkungan para siswa. Keywords: Standart Arabic, Slang Arabic and Diglossia.